Gaetano De Sanctis and Livy. The First Decade - Ridley, Ronald T. (Histos, 2014)
The classic history of the Roman republic in the twentieth century is Gaetano De Sanctis' Storia dei Romani, although it reached only to 134 BC. The most important source for that history is, of course, Livy's ab urbe condita. De Sanctis' attitude to Livy is therefore of interest. He began with a devastating assessment, and that is borne out throughout his own narrative, where Diodoros is almost always preferred. When De Sanctis came, however, to reconstruct Rome's history, he proposed the most radical revisions of the tradition, usually relying on Livy!